A new species of the alpheid shrimp genus Salmoneus Holthuis, 1955 (Decapoda: Caridea) from the Seto Inland Sea, Japan - Komai, Tomoyuki (Zootaxa, 2022)
A new species of the alpheid shrimp genus Salmoneus Holthuis, 1955 is described based on two specimens from the Seto Inland Sea, Japan. Salmoneus aduncus n. sp. is strikingly similar to S. rostratus Barnard, 1962, which is distributed widely in the tropical Indo-West Pacific, but the new species is distinguished from the latter by the proportionally wider telson, the less pronounced longitudinal grooves on the major cheliped palm, and the weaker occlusal teeth on the major cheliped fingers. The living colouration is also different between the two. Phylogenetic analysis using the mitochondrial 16S rRNA gene supports the recognition of the new species. Salmoneus is primarily distributed in tropical and subtropical waters, and in temperate waters in East Asia, only S. gracilipes Miya, 1972, has been the sole representative of the genus. The new species is the second to be recorded from the warm temperate areas in East Asia, although its real distribution remains to be clarified.